Novatian, Presbyter of Rome and Anti-Pope(251 – 258) (Forum Theologicum Sardicense, 2025)
Fr. Stephan Staykov, Novatian, Presbyter of Rome and Anti-Pope (251 – 258). In the middle of the third century, the Church was once again compelled to address the suffering caused by fraternal division and the spiritual destruction resulting from schismatic movements that originated and developed in the Western Church. The cause of this schism was the Roman presbyter Novatian. Born in the early third century, Novatian was likely of Roman origin. He was well-known in his time primarily as a church writer and one of the early Latin theologians. Of his many writings, only two have survived: “On the Trinity” and “On the Food of the Jews. Novatian's extreme rigor led him into schism, and he died as a martyr in 258. His followers persisted until the eighth century.
Keywords: Early Christianity; Roman Empire; Cyprian of Carthage; Novatian; Pope Cornelius; Rome; Carthage; Italy; Africa